Conventional and Islamic Equity Market Reaction Towards Terrorism: Evidence Based on Target Types, Location and Islamic Calendar Months - Irshad, Hira; Taib, Hasniza Mohd; Hussain , Haroon; Hussain, Rana Yassir (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2023)
This study investigates the conventional and Islamic equity market reaction towards terrorism events in Pakistan from 2009 to 2016 using OLS regression and GARCH (1, 1) models. The prospect theory and efficient market hypothesis are the relevant theories. Findings indicate that conventional and Islamic equity market reaction towards terrorism events is very short lived and markets recovers quickly. This study also documents the market reaction to terrorism events based on the target type, location and during the Islamic calendar months. The impact of different target types and different event locations on the conventional and Islamic equity markets varies. The equity markets in Pakistan responds negatively to the attacks on educational institutes and businesses whereas positively to attacks on armed forces’ facilities. Furthermore, conventional equity market responds negatively to terrorist attacks in Karachi and positively to attacks in financial cities and FATA. Interestingly, Islamic equity market responds positively towards the attacks in financial cities and FATA, however, with very minute reaction magnitude. The findings of this study are useful for the investors to manage their portfolios by considering magnitude and direction of market reaction towards terrorism based on the target type, location and Islamic months. Overall, this study concludes that conventional and Islamic equity markets reaction towards terrorism is very minute; however, the conventional and Islamic equity markets reaction varies based on target type, event location and different Islamic calendar months. Furthermore, the findings also suggest that equity markets recover very soon, therefore, markets are efficient in observing these shocks.